The relevance of Geographic Information Systems (SIGs) in Professional and Technological Education (EPT): the contribution of Geography to the consolidation of this knowledge (Research, Society and Development, 2020)
The Geographic Information Systems (GIS) are products of technological advances that society has produced throughout human history, mainly from the middle of the 20th century, results mainly from the creation of computers and their constant modernization. The purpose of this article is, therefore, to encourage the use of these information systems as a pedagogical resource in the process of teaching and learning Geography, especially in Vocational and Technological Education (EPT). The use of computational tools has been progressively important in solving the socio-spatial problems that afflict society, collaborating with urban planning and the environmental management of natural resources. Geography is one of the sciences that best use this knowledge, mainly in the teaching of geographic contents. It is also defended in this research the use of these technological tools in the resolution of the problems arising from wrong planning by the public managers. In addition, they can also be used for suggestions for improving geographic space. The article has a bibliographic character working with authors who deal with the characterization of GIS in several aspects, such as conceptualization, structure and use. SIGs are a set of programs that can, if used and methodologically well structured, contribute to improving the quality of Geography teaching, especially at EPT.